2018
DOI: 10.1038/s41598-018-25951-2
|View full text |Cite
|
Sign up to set email alerts
|

Illusory body ownership of an invisible body interpolated between virtual hands and feet via visual-motor synchronicity

Abstract: Body ownership can be modulated through illusory visual-tactile integration or visual-motor synchronicity/contingency. Recently, it has been reported that illusory ownership of an invisible body can be induced by illusory visual-tactile integration from a first-person view. We aimed to test whether a similar illusory ownership of the invisible body could be induced by the active method of visual-motor synchronicity and if the illusory invisible body could be experienced in front of and facing away from the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 39 publications
3
52
1
1
Order By: Relevance
“…The body representation is malleable: e.g., (Lackner, 1988;Ramachandran and Hirstein, 1998;de Vignemont et al, 2005;Ehrsson et al, 2005b;Longo et al, 2009a) Non-bodily objects can be embodied: e.g., (Botvinick and Cohen, 1998;Slater et al, 2008;Petkova et al, 2011a;Nishio et al, 2012Nishio et al, , 2018Ogawa et al, 2012;Guterstam et al, 2013Guterstam et al, , 2015Caspar et al, 2015;Kilteni et al, 2015;Ma and Hommel, 2015a;van der Hoort and Ehrsson, 2016;Aymerich-Franch et al, 2017a;Jazbec et al, 2017;Liepelt et al, 2017;Weser et al, 2017;Kondo et al, 2018a) 2. Embodiment can be evoked by mediated sensorimotor interaction Embodiment can be evoked by mediated: -visuotactile stimulation: e.g., D'Alonzo and Cipriani 2012; (Petkova and Ehrsson, 2008;Slater et al, 2008;Kilteni et al, 2012a;Maselli and Slater, 2013;Keizer et al, 2016;Krom et al, 2019) -visuomotor and proprioceptive cues: e.g., (Tsakiris et al, 2006;Dummer et al, 2009;Sanchez-Vives et al, 2010;Slater et al, 2010;Petkova et al, 2011a;Walsh et al, 2011;Kilteni et al, 2012b;Alimardani et al, 2013;Ma and Hommel, 2013;Maselli and Slater, 2013;…”
Section: The Body Representation Is Malleable and Can Include Non-bodmentioning
confidence: 99%
“…The body representation is malleable: e.g., (Lackner, 1988;Ramachandran and Hirstein, 1998;de Vignemont et al, 2005;Ehrsson et al, 2005b;Longo et al, 2009a) Non-bodily objects can be embodied: e.g., (Botvinick and Cohen, 1998;Slater et al, 2008;Petkova et al, 2011a;Nishio et al, 2012Nishio et al, , 2018Ogawa et al, 2012;Guterstam et al, 2013Guterstam et al, , 2015Caspar et al, 2015;Kilteni et al, 2015;Ma and Hommel, 2015a;van der Hoort and Ehrsson, 2016;Aymerich-Franch et al, 2017a;Jazbec et al, 2017;Liepelt et al, 2017;Weser et al, 2017;Kondo et al, 2018a) 2. Embodiment can be evoked by mediated sensorimotor interaction Embodiment can be evoked by mediated: -visuotactile stimulation: e.g., D'Alonzo and Cipriani 2012; (Petkova and Ehrsson, 2008;Slater et al, 2008;Kilteni et al, 2012a;Maselli and Slater, 2013;Keizer et al, 2016;Krom et al, 2019) -visuomotor and proprioceptive cues: e.g., (Tsakiris et al, 2006;Dummer et al, 2009;Sanchez-Vives et al, 2010;Slater et al, 2010;Petkova et al, 2011a;Walsh et al, 2011;Kilteni et al, 2012b;Alimardani et al, 2013;Ma and Hommel, 2013;Maselli and Slater, 2013;…”
Section: The Body Representation Is Malleable and Can Include Non-bodmentioning
confidence: 99%
“…In particular, Kokkinara et al [33] showed that in order to feel body ownership in VR, the synchronicity of visuotactile or visuomotor stimulation are needed, and that visuomotor feedback has more influence on body ownership than visuotactile stimulation. Despite the fact that it is possible to feel some ownership when seeing only virtual hands and feet [34], the avatar's appearance has been shown to be of importance to maximise the ownership illusion. For example, it is usually stronger with an avatar with coherent clothes or skin tone [45], and potentially even higher with a self-representation [21].…”
Section: External Factorsmentioning
confidence: 99%
“…Recent studies have raised further questions about the nature of embodiment [43]; specifically, how much of the body is required for an embodied experience. In one study, scholars found that an invisible body can still create a sense of body ownership [52]. However, more customized avatars enhanced ownership of the body as well as the feeling of presence in the virtual environment [53].…”
Section: Introductionmentioning
confidence: 99%